Sodium-glucose co-transporter inhibitor dapagliflozin attenuates cognitive deficits in sporadic Alzheimer’s rat model - KABASAKAL, LEVENT; YAVUZ, AYŞE NUR (My University, 2022)
© 2022 Marmara University Press.Alzheimer’s disease (AD) and Type 2 Diabetes Mellitus (T2DM) are both characterized by similar pathologies, and studies have shown that various drugs from both groups may be effective in another. The effects of sodium-glucose co-transporter (SGLT)2 inhibitors in AD are unknown. According to molecular docking studies, various SGLT inhibitors have acetylcholinesterase (AChE) inhibition activity, which is therapeutic target for AD. In this study, we investigated the effects of SGLT2 inhibitor dapagliflozin on intracerebroventricular (icv) streptozotocin (STZ) induced sporadic AD rats using open field test (OFT), novel object recognition test (NORT), passive avoidance test (PAT) and Morris’s water maze test (MWMT). Rats were randomly divided into 4 groups: vehicle-control, icv STZ, dapagliflozin, and galantamine treatments groups. STZ was injected bilaterally in two divided doses on day 1 and 3. All treatments began on day 1 and continued to day 21. OFT was performed for evaluating animal locomotor activity and anxiety. Other behavioral tests, NORT, PAT, and MWMT was performed for determining of learning and memory ability of rats. On day 21, all rats were decapitated. Our results showed that treatments with dapagliflozin and galantamine significantly prevented learning and memory deficits in behavioral tests. Dapagliflozin may present as a potent dual inhibitor of SGLT2 and AChE. Our results may form the basis of future dual treatment against diabetes and diabetes-related neurological diseases. The effects of possible dual AChE and SGLT2 inhibition by a single compound may help to establish new drugs that perform both anti-AD and antidiabetic action.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Alzheimer’s disease; Dapagliflozin; sodium-glucose co-transporter inhibitor; type 2 diabetes mellitus; Dapagliflozin; Alzheimer’s disease; type 2 diabetes mellitus; sodium-glucose co-transporter inhibitor